2020
DOI: 10.2147/dddt.s222694
|View full text |Cite
|
Sign up to set email alerts
|

<p>Genipin Induces Autophagy and Suppresses Cell Growth of Oral Squamous Cell Carcinoma via PI3K/AKT/MTOR Pathway</p>

Abstract: Background: Oral squamous cell carcinoma (OSCC) is a common malignant tumor of the head and neck, and it accounts for more than 90% of oral cancer. Due to high mortality, limitations of traditional treatment and many complications, new treatment methods are urgently needed. This study aimed to look into the effect of new potential anti-tumor drug, genipin, on OSCC treatment. Methods: In vitro, CCK-8, colony formation, and flow cytometry were used to detect the effect of genipin on SCC-9 and SCC-15 cell lines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 38 publications
1
21
1
Order By: Relevance
“…Oral squamous cell carcinoma (OSCC) accounts for 90% oral malignancies, characterized by high aggressive and early lymph node metastasis [ 1 3 ]. According to the latest GLOBOCAN 2019 report, the number of new cases of oral cancer in 2019 is 53,000, and the death toll is 10,860 in the United States [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) accounts for 90% oral malignancies, characterized by high aggressive and early lymph node metastasis [ 1 3 ]. According to the latest GLOBOCAN 2019 report, the number of new cases of oral cancer in 2019 is 53,000, and the death toll is 10,860 in the United States [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…4C and D). Some previous studies suggested that genipin can induce autophagy through the p53-DRAM signaling pathway in gastric cancer treatment or via the PI3K/AKT/mTOR signaling pathway in oral squamous cell carcinoma treatment [39,40]. Herein, genipin was also con rmed to induce autophagy, which may further be involved in regulating Tau phosphorylation.…”
Section: Discussionmentioning
confidence: 81%
“…PI3K/AKT is a potent pathway to activate and trigger cell survival signals, which play a crucial role in apoptotic cell death associated with chemotherapeutic drug treatment. 28,29 Dysregulation of this pathway is also related to the therapeutic resistance of glioma. 30 With that, our results demonstrated that β-mangostin resulted in a significant induction of apoptosis and in a concomitant reduction of Akt phosphorylation at Ser473, which consequently inhibited PI3K/AKT/mTOR signaling pathway in C6 cells.…”
Section: Discussionmentioning
confidence: 99%